How the role of ATM technology encourage financial efficiency on Madura villagers? - Alifah Rokhmah Idialis; Sariyani Sariyani; Ayu Delawati Prasetyoningtyas; Roechainy Kartika Ulfa (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2021)
Nowadays, the necessity and utilization of Automatic Teller Machine (ATM) technologies increase in rural areas.  Financial technology became a crucial thing and created efficiency in their activities. Some previous research uncovers technology that could create efficiency in the economy, including financial technology. This paper, interest in investigating and detect how ATM technology establishes financial efficiency on villagers. This research was conducted in rural communities on the island of Madura, Indonesia. This study uses SFA (Stochastic Frontier Analysis) model to estimate technical efficiency. This research found out that ATMs in rural communities on Madura Island produce highly financial efficiency. It proved that the villagers in Madura need ATM technology for carrying out their economic activities.